Nieetatowe rozwiązanie karierowe jako sposób gromadzenia kapitału kariery - Litaszewska, Elwira (Studia Edukacyjne, 2017)
The structure of the study was subordinate to the question about the characteristics of career choices undertaken in the discourse of lifelong learning and career planning. The distinguishing mechanisms for selected career development approaches emphasize the importance of entrepreneurial attitudes and the effective use of personal resources. The accumulation of career capital can be a response to the demands of the modern labor market and to the dynamics of the changes taking place within it. This approach is quite strongly focused on non-career career choices, exemplified by start-ups.